Register Form at Semarang Shipping Vocational School - Baehaqie, Imam; Ardiningsih, Monitha (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Language as a communication tool has an important role in human interaction. If the language variations seen in terms of the usage in each environment or group are usually marked with registers. In Semarang Shipping Vocational School there is a shipping register that is not found in other public schools. The purpose of this study is to analyze the form of registers in Vocational High School Shipping Semarang. This qualitative-descriptive research uses accidental sampling data collection techniques or unplanned techniques. The source of the research data is the conversations of the residents of Semarang Shipping Vocational School. The data in this study are fragments of conversations between Vocational Vocational High School residents who allegedly contain a form of shipping register. The data analysis technique used descriptive analysis of the interactive model. Presentation of the results of data analysis using informal data presentation. The shipping register data at SMK Pelayaran Semarang is 118 and has been identified in the form of 43 basic words, 9 affixes, 11 acronyms and abbreviations, and 55 phrases. The trend of the shipping register form at the Semarang Shipping Vocational School is in the form of phrases. This research is important for (1) Indonesian language teachers, because the use of language is not limited to what is written in the dictionary, but also using written language in the shipping register language, (2) for cadets, there are other languages that must be mastered, especially in shipping world.